Analysis of the Role and Function of Foundations in Realising Private Higher Education that is Free From Corruption, Collusion, and Nepotism towards Good University Governance - Rina Rohayu Harun; Nurjannah Septyanun; Ufran; Muslim (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyse the factors that influence the occurrence of corruption, collusion, and nepotism in private higher education foundations; Analyze the supervision and control mechanisms implemented by foundations to prevent corruption, collusion, and nepotism and determine the legal construction of the role and function of foundations in private higher education institutions that are free from corruption, collusion, and nepotism based on Good University Governance (GUG). This research is an empirical-normative legal study, complemented by empirical data. The research was conducted for 1 (one) month, starting from March 20 to April 20, 2025. The respondents were 5 (five) representatives of the foundation's management, the vice chairman of the academic institution, lecturers, and employees. The results of this study indicate that the practice of Corruption, Collusion, and Nepotism in private higher education foundations is caused by several primary factors such as lack of transparency and accountability, the dominance of certain families or groups, weak supervision, low leadership ethics, inconsistency of regulations with practices, internal political competition, and economic motives. To overcome this, foundations must implement strict monitoring and control mechanisms, including open recruitment, establishing internal monitoring units and external audits, transparency of financial reports, applying sound governance principles, and enforcing codes of ethics and whistleblowing systems. In the legal context, the role and function of foundations must be constructed based on the principles of Good University Governance (GUG), which makes foundations not only legal entities that organise education, but also motors of governance that are integrated, transparent, and accountable by applicable laws and regulations Keywords: Role and Function of Foundations, Corruption, Collusion, Nepotism (KKN), Good University Governance (GUG)